Dissociating memory traces and scenario construction in mental time travel. (January 2016) - Cheng, Sen; Werning, Markus; Suddendorf, Thomas
Highlights: Mental time travel (MTT) involves the construction of scenarios. Scenarios contain information about participants, settings, interactions and events. Scenarios are constructed based on episodic memory traces and semantic information. Some nonhuman animals appear to encode, store and retrieve episodic memory traces. Only humans seem to construct, reflect and flexibly compare alternative scenarios. Abstract: There has been a persistent debate about how to define episodic memory and whether it is a uniquely human capacity. On the one hand, many animal cognition studies employ content-based criteria, such as the what-where-when criterion, and argue that nonhuman animals possess episodic memory. On the other hand, many human cognition studies emphasize the subjective experience during retrieval as an essential property of episodic memory and the distinctly human foresight it purportedly enables. We propose that both perspectives may examine distinct but complementary aspects of episodic memory by drawing a conceptual distinction between episodic memory traces and mental time travel. Episodic memory traces are sequential mnemonic representations of particular, personally experienced episodes. Mental time travel draws on these traces, but requires other components to construct scenarios and embed them into larger narratives. Various nonhuman animals may store episodic memory traces, and yet it is possible that only humans are able to construct and reflect on narratives of their lives – and flexibly compare alternative scenarios of the remote future.